Complex Behavior of Droplet Transfer and Spreading in Cold Metal Transfer - Shuai Yang; Yanfeng Xing; Fuyong Yang; Juyong Cao (Shock and Vibration)
In intelligent manufacturing, an intelligent control method of welding process is an important process of intelligent welding manufacturing technology (IWMT). Metal transfer is a key factor to control the welding process. Metal transfer and droplet spreading are of vital importance for welding formation. A new theoretical model of cold metal transfer (CMT) in short-circuit transfer mode is proposed in this paper. In this model, the CMT welding process is regarded as a continuous process of arc heating, mass transfer, short-circuit, and spreading, and the relations between these processes are analyzed. The calculation equations used by the model can analyze the welding formation clearly and simplify the complex welding process into continuous physical behavior. The predicted welding width shows good agreement with the measurement results. The mechanism of increased welding width is also comprehensively analyzed. Results have a certain guiding effect on aluminum alloy welding process control.